The dead of winter : three Giordano Bruno novellas - Parris, S. J., 1974- (Parris, S. J., 1974- Giordano Bruno thriller, 2020)
Three exhilarating novellas 'The Secret Dead, The Academy of Secrets, and The Dead of Winter' following the early adventures of young priest Giordano Bruno in the dramatic days of sixteenth century Italy. Even the dead have a story to tell ... Naples, 1566. During a sweltering summer, eighteen-year-old Giordano Bruno takes his final vows at San Domenico Maggiore and is admitted to the Dominican Order despite doubts over his tendency to ask difficult questions. Assisting in the infirmary, Bruno witnesses an illicit autopsy performed on the body of a young woman. Her corpse reveals a dark secret, and Bruno suspects that hers may not have been an accidental death. His investigation leads him to a powerful figure who wants to keep the truth buried and Bruno is forced to make a choice between his future in the Order, and justice for an innocent victim and her grieving family.